Acute onset anarthria in a 7-year-old patient as a presentation of acute disseminated encephalomyelitis: A rare clinical and radiological entity - Rachid Belfkih, Professor of neurology; Omar Ghomari Khayat, MD (Radiology Case Reports, 2021)
Acute disseminated encephalomyelitis (ADEM), also called post-infectious encephalomyelitis, is defined as an immune-mediated inflammatory and demyelinating event that involves the central nervous system. It usually follows an infectious episode or an active immunization several weeks prior the disease onset. ADEM is typically presented with an encephalopathy associated to focal neurological signs. Cerebrospinal fluid analysis is usually nonspecific, showing signs of central nervous system inflammation with negative viral and bacterial cultures. The diagnosis is based on clinical and MRI findings. Patients with ADEM respond well to anti-inflammatory and immunosuppressive agents, with high-dose of intravenous steroids administered as first-line treatment. Herein, we present the case of a 7-year-old male patient diagnosed of acute disseminated encephalomyelitis most likely secondary to a viral upper respiratory tract infection. It is a unique case, as the inaugurating sign is an acute onset anarthria. The patient responded favorably to the first-line therapy with an almost full recovery within the first week of treatment.